The Relationship between Career Maturity and Anxiety in Facing the World of Work in Final Year Students at University - Permatasari, Fanny; Oktavianita, Sri; Simamora, Anastasia (Lafadz Jaya Publisher, 2024)
This research uses a quantitative approach with a correlation method involving 103 respondents using convenience sampling. The data obtained was processed using Pearson's Parametric Test of Correlation calculations in IBM SPSS Statistics 20. The results of this study show a contribution value of -0.617, which means there is a negative relationship between career maturity and anxiety about facing the world of work. This can be interpreted as the higher the career maturity, the lower the anxiety in facing the world of work. On the other hand, the lower the career maturity, the higher the anxiety about facing the world of work. This research also found that factors such as social support, work experience, and education level play a significant role in influencing an individual's career maturity and anxiety level. The implications of these findings suggest the need for more intensive career guidance programs and psychological support for individuals newly entering the workforce to reduce their anxiety levels. Thus, developing career maturity not only impacts individuals' readiness to face work challenges, but also contributes to their psychological well-being.